Organotypic and primary neural cultures as models to assess effects of different gold nanostructures on glia and neurons. Issue 3 (16th March 2019) - Ji, Jeff; Moquin, Alexandre; Bertorelle, Franck; KY Chang, Philip; Antoine, Rodolphe; Luo, Julia; McKinney, R. Anne; Maysinger, Dusica
Abstract: Gold nanoparticles (AuNP) have unique physicochemical properties and have been used as delivery vehicles, contrast agents, and therapeutic compounds. Although the effects of AuNPs on peripheral tissues and immortalized cell lines have been extensively characterized, their effects on the central nervous system (CNS) are predominantly unknown. The main objective of the current study was to evaluate how AuNPs of varying sizes (1–100 nm), shapes (clusters, spheres, rods, flowers), and surfaces impact synaptic structures in the hippocampus, a brain structure often affected in neurodegeneration. Using a combination of organotypic hippocampal, as well as, primary neuronal, glial, and astrocytic cultures, we examined AuNPs impact on hippocampal dendritic spine density, internalization in various neural cells, and lysosomal status in astrocytes. Considering that neurons interact with astrocytes, and that lysosomes play a role in dendritic spine status, transcription factor TFEB and abundance of lysosomal marker, LAMP1 were evaluated. Both biomarkers were significantly increased in astrocytes exposed to AuNPs, suggesting that AuNPs not only enter lysosomes, but also increase lysosome biogenesis. Results from our studies show that AuNPs with poly(ethylene glycol) (AuNPs-PEG) or glutathione (AuNP-GSH) surfaces do not substantially decrease hippocampal dendritic spine density. Conversely, AuNPs coated with the detergent, CTAB, significantly decreased total spine density. Interestingly small gold nanoclusters (Au15 (SG)13 ) with GSH reduced spine density, whereas larger gold nanoclusters (Au25 (SG)18 ) with the same ligand did not. Thus, assessment of dendritic morphology, spine densities can reveal subtler changes of neural cells than cell death when exposed to nanoparticles, including AuNPs.